Thai Society In Perspective Of The Carvaka Philosophy - Punsri, Phramaha Teerawee; Chatongyots, Laongdao (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This article aims to analyze Thai society through the lens of the Charvaka philosophy, reflecting the characteristics of Thai society that are marked by haste, enjoyment, entertainment, and indulgence. It highlights issues such as poor-quality education, politics driven by self-interest, and a superficial cultural tradition devoid of true value, focusing solely on materialism. According to the Charvaka philosophy, the present is to be lived fully, with no concern for an afterlife or future reincarnation. It advocates for indulgence in sensory pleasures, emphasizing eating, drinking, and seeking happiness in this life because the afterlife is uncertain. The Charvaka philosophy, or materialistic philosophy, promotes the pursuit of immediate gratification by satisfying bodily desires without regard for moral principles. This results in concepts such as materialism, hedonism, and the pursuit of bodily pleasures. It leads people to focus on enjoying the present without concern for life after death, as there is no influence on current existence—once death comes, it is the end. The philosophy prioritizes material possessions over the mind, advocating for reducing suffering and increasing just happiness.